2022
DOI: 10.1177/02841851221095238
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of diagnostic reference levels in low-dose renal computed tomography

Abstract: Background Increased radiation doses from computed tomography (CT) examinations is well known with proven risks of inducing cancers for effective dose >100 mSv (according to some studies >50 mSvs). Purpose To establish the diagnostic reference level (DRL) for low-dose renal CT examinations in the evaluation of renal stones. Material and Methods Patient demographics, CT parameters, and dosimetric indices (CTDIvol and dose length product [DLP]) were collected from 12 tertiary hospitals that routinely perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The DRL values for CT examinations were reported in six studies: two reported the DRLs for children (Rawashdeh et al 2019; Rawashdeh et al 2023); one reported the DRL for cardiac CT examinations (Rawashdeh et al 2019); one reported the DRL for renal CT (Rawashdeh and Saade 2023) examinations; and the last two were reported DRLs for CT of chest, abdomen, pelvis, and brain CT (Radaideh et al 2023; Al Ewaidat et al 2018). All studies determined the DRL values of the CT scans using patient level data.…”
Section: Resultsmentioning
confidence: 99%
“…The DRL values for CT examinations were reported in six studies: two reported the DRLs for children (Rawashdeh et al 2019; Rawashdeh et al 2023); one reported the DRL for cardiac CT examinations (Rawashdeh et al 2019); one reported the DRL for renal CT (Rawashdeh and Saade 2023) examinations; and the last two were reported DRLs for CT of chest, abdomen, pelvis, and brain CT (Radaideh et al 2023; Al Ewaidat et al 2018). All studies determined the DRL values of the CT scans using patient level data.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Increased levels of computed tomography (CT) scan-produced radiation doses are statistically proven to cause carcinomas for >100 mSv effective doses (and >50 mSvs as well as seen in some other research). [19] Recent advances in CT have been greatly helpful for the diagnosis of urolithiasis however due to the increasing frequency and rate of recurrence of renal tract stones, grey scale sonography is not the imaging modality of choice in comparison to CT scan KUB for demonstration and evaluation of urinary tract stones. [14] Repeated hospital visits may occur in many of the patients with renal area pain, requiring radiological investigations recurrently, it should be a matter of concern that collective dose due to radiation exposure must remain within permissible limits.…”
Section: Discussionmentioning
confidence: 99%